POLA KONSUMSI PANGAN MASYARAKAT BERBASIS KARBOHIDRAT DI KOTA BENGKULU: APLIKASI MODEL AIDS - Kencana, Felycia Tiera; Sukiyono, Ketut; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Analysis of patterns of food consumption of carbohydrate-based society in the city of Bengkulu aims to determine the pattern of food consumption, identify factors - factors that affect carbohydrate-based food consumption in the city of Bengkulu and to determine the elasticity of consumption of rice and tubers at their own price, cross and income. This study uses analysis of almost ideal demand system (AIDS) and the elasticity of demand. The sample used in this study is the survey data SUSENAS (Socio-Economic Survey) In 2012 as many as 292 households. The results of this study were (1) Patterns of food consumption of carbohydrates in the city of Bengkulu showed that total rice consumption expenditures greater than the bulbs, which is USD 61.021,71 / week and tuber 26.617,43 USD / week. Factors affecting food consumption patterns of carbohydrate in Bengkulu city is the economic factor. The economic factor is the price of food consumed requirement itself. Price elasticity is performed on the combined restriction on both rice and tubers food sources are unitary inelastic, inelastic cross elasticity and income elasticity is unitary elastic.